Effects of fiber orientation of adjacent plies on the mode I crack propagation in a carbon-epoxy laminates - Mohamed Rehan, Muhammad Saifuddin (Elsevier, 2011)
The influence of ply orientation on the resistance to mode I delamination of multidirectional composite laminates can be assessed by Double Cantilever Beam (DCB) tests. However, one of the difficulties associated with such a study is the change in overall elastic parameters occurring when modifying local ply orientations. The present work uses laminates with special stacking sequences allowing for isolating the orientation parameter. Multidirectional DCB specimens were designed so as to obtain an uncoupled quasi isotropic and quasi-homogeneous elastic behavior, with the same properties for the entire laminate and the two sub laminates separated by the pre crack at mid-plane. The results show that the toughness in term of GIC is slightly affected by the variation of ply orientations at the crack interface. The differences are more pronounced in the crack propagation behavior after the initiation point. Even with the same orientation at the crack interface, different subsequent ply orientations can also lead to different crack resistance behavior.